Between Scores and Reality: Assessing the Impact of Islamic Religious Education on Students’ Religious Character in Elementary Schools - Nurhikmah; Ibnu Imam Al Ayyubi; Firda Noerzanah; Shoutika Nawadya Ikromi; Syed Muhammad Adib Termizi b Ahmad al-Jafari (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study was conducted to analyze the learning approaches used in Islamic Religious Education (PAI) at the elementary school level and their role in shaping students’ religious character. The research was motivated by the ongoing gap between students’ mastery of religious knowledge and the internalization of Islamic values in daily life, as many students achieve high academic scores in PAI but still display behaviors that are inconsistent with Islamic teachings. Using a mixed-methods approach with an explanatory sequential design, the study involved 120 students from three elementary schools MI Madani, MIS Al-Bashirah, and SD Inpres Mannurukki. Quantitative data were obtained from PAI learning outcomes, while qualitative data were collected through in-depth interviews and classroom observations to provide contextual insights into the quantitative findings. The quantitative analysis showed no statistically significant correlation (p > 0.05) between PAI learning outcomes and students’ achievements in cognitive subjects such as mathematics and science. However, qualitative findings revealed that PAI teachers applied various strategies emphasizing value internalization, including storytelling, group discussions, reflective learning, and the “One Day One Verse” program, which successfully enhanced students’ enthusiasm, engagement, and moral awareness. These results indicate that PAI learning functions not only cognitively but also affectively and spiritually. In conclusion, reflective, contextual, and interactive learning approaches in PAI contribute substantially to developing students’ understanding and practice of Islamic values. The novelty of this study lies in integrating mixed-method evidence to demonstrate that the formation of religious character depends more on pedagogical approach and teacher commitment than on academic achievement alone. Therefore, strengthening teacher capacity and institutional support is essential to advancing holistic and value-based Islamic education.